Preliminary Observations on the Pathogenesis of a Virulent Strain of Newcastle Disease Virus in Chickens - Singh, K. V. (1971)
Development of Newcastle disease, after experimental and natural infection with the virulent strain VLT of Newcastle disease virus, and its growth and distribution in some selected tissues as assayed by the enumeration of plaques are reported.